Kestasioneran Kurs Dolar Amerika dan Harga Saham Pada Masa Pandemi Covid 19 Tahun 2020 - Rahimullaily, Rahimullaily; Amalina, Amalina (JOSTECH: Journal of Science and Technology, 2021)
This study aims to determine the stationarity of the US dollar exchange rate and stock prices during the Covid 19 pandemic. One of the interesting stocks to study is the stock price of PT Telecommunications Indonesia Tbk. The augmented Dickey-Fuller test was used to determine the stationarity of the two variables. The research data is sourced from secondary data through the official website of Bank Indonesia to view the US Dollar Exchange Rate and through the website investing to see the stock price of PT. Telekomunikasi Indonesia Tbk during the Covid 19 pandemic period in Indonesia occurred from March to December 2020. The results showed that the check of the stationary stock price of PT. Telekomunikasi Indonesia Tbk and the US Dollar exchange rate at level I (0) was not stationary. While the two variables are stationary in the first differencing conditions I (1).